Community Empowerment Strategy for the Development of Small Business Units in Indonesia - New Guinea Border Region - Pakasi, Usman (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the strategy of community empowerment in border areas. It was conducted through the utilization of processed catfish for the development of economic and small-scale business units in the border regions of Indonesia and Papua New Guinea. The method used was the descriptive qualitative method. Data collection techniques were applied through observation, interviews, and Focus Group Discussions (FGD). The results showed that the catfish aquaculture assistance program in the border region has a significant potential to encourage the development of community commercial business units. Utilization of catfish aquaculture production has been a primary mate .This study aims to analyze the strategy of community empowerment in border areas. It was conducted through the utilization of processed catfish for the development of economic and small-scale business units in the border regions of Indonesia and Papua New Guinea. The method used was the descriptive qualitative method. Data collection techniques were applied through observation, interviews, and Focus Group Discussions (FGD). The results showed that the catfish aquaculture assistance program in the border region has a significant potential to encourage the development of community commercial business units. Utilization of catfish aquaculture production has been a primary material for making several kinds of food products. Some products that are produced from processed catfish meat, namely shredded catfish, catfish meatballs, catfish chips, and catfish nuggets.It is a kind of essential economic empowerment for border areas. Such empowerment programs have opened up opportunities for economic growth, and therefore, is suggested to be implemented in the other area.